The Role of X-Ray Diffraction for Analyzing Zr-Sn-Nb-Fe Alloys as Power Reactor Fuel Cladding - Sugondo Sugondo (Atom Indonesia, 2010)
Synthesis of Zr-1%Nb-1%Sn-1%Fe alloy is undertaken in order to develop fuel cladding alloy at high burn-up. Powder specimens of Zr-Sn-Nb-Fe alloy were prepared and then formed into pellets with a dimension of 10 mm in height 10 mm in diameter using a pressure of 1.2 ton/cm2. The 5 gram green pellets were then melted in an arc furnace crucible under argon atmosphere. The pressure in the furnace was set at 2 psi and the current was 50 A. Afterwards, the ingots were heated at a temperature of 1100°C for 2 hours and subsequently quenched in water. The ingots then underwent annealing at temperatures of 400°C, 500°C, 600°C, 700°C, and 750°C for 2 hours. The specimens were analyzed using X-ray diffraction in order to construct diffractograms. Results of the diffraction patterns were fitted with data from JCPDF (Joint Committee Powder Diffraction File) to determine the type of crystals in the elements or substances. The greater the crystallite dimension, the smaller the dislocation density. Agreeable results for hardening or strengthening were obtained at annealing temperatures of 500°C and 700, whereas for softening or residual stress at 600°C and 750°C. The nucleation of the secondary phase precipitate (SPP) was favourable at annealing temperatures of 400°C, 500°C, and 700°C. For Zr-1%Nb-1%Sn-1%Fe alloy with annealing temperatures between 400°C to 800°C, precipitates of Fe2Nb, ZrSn2,FeSn, SnZr, NbSn2, Zr0.68Nb0.25Fe0.08, Fe2Nb0.4Zr0.6, Fe37Nb9Zr54, and ω-Zr were observed. Satisfactory precipitate stabilization was achieved at annealing temperature of 800°C, growth of precipitates at temperature between 500°C to 600°C, and minimization of precipitate size at 700°C.Received: 20 November 2009; Revised: 31 August 2010; Accepted: 31 August 2010